2002
DOI: 10.1071/ar00121
|View full text |Cite
|
Sign up to set email alerts
|

The production and storage of a fermentor-grown bacterial culture containing Synergistes jonesii, for protecting cattle against mimosine and 3-hydroxy-4(1H)-pyridone toxicity from feeding on Leucaena leucocephala

Abstract: The leguminous shrub Leucaena leucocephala (leucaena) iswidely used as a forage species for cattle in tropical agriculture. However,leucaena contains the toxic amino acid mimosine. Both mimosine and its primaryruminal degradation product 3-hydroxy-4(1H)-pyridone (DHP) are toxic and theiraccumulation in the animal’s system results in hair loss, reducedliveweight gain, and goitre. The ruminal bacteriumngle cultivar bywithholding water. In Expt 2, plants of EP and MK were grown together in thesame container and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 16 publications
2
24
0
1
Order By: Relevance
“…With the movement away from the use of chemicals and antibiotics in modern animal agriculture it is imperative that alternative processes are found that will maintain levels of production and feed utilization efficiency. The use of live microbes as inocula to manipulate the rumen ecosystem is one such process and the success of the microbial inocula containing Synergistes jonesii to protect cattle feeding on Leucaena leucocephala , from mimosine poisoning (Klieve et al. 2002), demonstrates that it can be a practical solution.…”
Section: Discussionmentioning
confidence: 99%
“…With the movement away from the use of chemicals and antibiotics in modern animal agriculture it is imperative that alternative processes are found that will maintain levels of production and feed utilization efficiency. The use of live microbes as inocula to manipulate the rumen ecosystem is one such process and the success of the microbial inocula containing Synergistes jonesii to protect cattle feeding on Leucaena leucocephala , from mimosine poisoning (Klieve et al. 2002), demonstrates that it can be a practical solution.…”
Section: Discussionmentioning
confidence: 99%
“…Igualmente, el FP utilizado como factor de eficiencia microbiana no se vio afectado. Se ha demostrado que los rumiantes pueden tolerar hasta 30% de leucaena en la dieta sin tener un impacto negativo en la producción (Yami et al, 2000;Ghosh et al, 2007); este efecto se ha atribuido, en parte, a la capacidad de ciertas bacterias del rumen de degradar mimosina y sus metabolitos (Klieve et al, 2002).…”
Section: Parámetros De Fermentación Y Producción De Metanounclassified
“…The rumen bacterium Synergistes jonesii, introduced into Australia in 1983, was shown to completely and rapidly degrade these toxins to safe levels (Jones and Megarrity 1986). Since 1996, an inoculum has been produced in vitro and made commercially available to Australian graziers (Klieve et al 2002). Accordingly, the issue of leucaena toxicity in Australia was thought to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Raymond Jones, in the early 1980s, discovered the 'leucaena bug' in the rumen of goats in Hawaii that degraded these toxic DHP metabolites into non-toxic compounds (Jones and Lowry 1984), which was named Synergistes jonesii (Allison et al 1992). Subsequently, a rumen inoculum containing S. jonesii was used as an 'oral drench' for cattle, kept in continuous culture (Klieve et al 2002) and supplied to farmers to dose cattle foraging on leucaena.…”
Section: Introductionmentioning
confidence: 99%